Effective Conservation of Desert Riverscapes Requires Protection and Rehabilitation of In-Stream Flows With Rehabilitation Approaches Tailored to Water Availability - Pennock, Casey A.; Budy, Phaedra; Macfarlane, William W. (Frontiers in Environmental Science, 2022)
Desert riverscape rehabilitation practitioners must contend with compounding effects of increasing human water demand, persistent drought, non-native species establishment, and climate change, which further stress desert riverine ecosystems such as rivers in the Colorado River basin, USA. Herein, we provide our perspective on the importance of natural flows, large floods in particular, for successful conservation and rehabilitation of riverscapes. We present ideas developed from our experience with rehabilitation projects across multiple desert tributary rivers with varying levels of habitat degradation and water abstraction. We propose spatially extensive measures such as protection of in-stream flows, tailoring rehabilitation efforts to available annual water availability, and working with nature using low-tech process-based techniques to more completely address the mechanisms of habitat degradation, such as flow reduction and vegetation-induced channel narrowing. Traditionally, rehabilitation efforts in the Colorado River basin take place at relatively small spatial extents, at convenient locations and, largely focus on reducing non-native plant and fish species. We suggest that we need to think more broadly and creatively, and that conservation or recovery of natural flow regimes is crucial to long-term success of almost all management efforts for both in-stream and riparian communities.